2012
DOI: 10.3109/13880209.2012.715170
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antioxidant properties of selectedScutellariaspecies from the Western Ghats of Peninsular India

Abstract: Scutellaria species of Western Ghats showed cytotoxic and antioxidant potential and the presence of baicalein. This suggests that S. colebrookiana and S. violacea could be used as alternative sources for baicalein in view of the reported scarcity of S. baicalensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The lymphatic cells are able to overcrowd, invade, and destroy lymphoid tissues and metastasize to other organs. Several studies have demonstrated that S. baicalensis , baicalin and baicalein display antiproliferative and apoptotic effects against lymphoma [17,54,55]. Huang et al reported that baicalin is capable of suppressing the growth of CA46 Burkitt lymphoma cells via induction of apoptosis with an IC 50 value of 10 μM [56].…”
Section: 5 Lymphomamentioning
confidence: 99%
“…The lymphatic cells are able to overcrowd, invade, and destroy lymphoid tissues and metastasize to other organs. Several studies have demonstrated that S. baicalensis , baicalin and baicalein display antiproliferative and apoptotic effects against lymphoma [17,54,55]. Huang et al reported that baicalin is capable of suppressing the growth of CA46 Burkitt lymphoma cells via induction of apoptosis with an IC 50 value of 10 μM [56].…”
Section: 5 Lymphomamentioning
confidence: 99%
“…7 This reaction depends on pH (optimum pH was 3.6). 8 FRAP methods performed at acidic pH conditions (3.6) for an iron solubility and the most important is to facilitate the transfer of …”
Section: Resultsmentioning
confidence: 99%
“…BL is used as a phytochemical marker for the quality control of Radix scutellariae in the Chinese pharmacopoeia, WL, B, W and OA are also major avonoids. It have been reported that they have anti-inammatory, 4,5 antioxidative, 6,7 antiallergic, 8 antiviral, 9 antigenotoxic, 10 anxiolytic 11 and anti-carcinogenic activities, 12,13 and have become the subjects of intense research interest. Kim et al have investigated the pharmacokinetic proles of BL, B, W and OA in rats aer intravenous administration of Scutellariae radix extract using LC-MS/MS.…”
Section: Introductionmentioning
confidence: 99%